Histopathologic Characterization of Peripheral Arteries in Subjects With Abundant Risk Factors - Torii, Sho; Mustapha, Jihad A.; Narula, Jagat; Mori, Hiroyoshi; Saab, Fadi; Jinnouchi, Hiroyuki; Yahagi, Kazuyuki; Sakamoto, Atsushi; Romero, Maria E.; Narula, Navneet; Kolodgie, Frank D.; Virmani, Renu; et al. (JACC. Cardiovascular imaging, 2019)
The aim of this study was to comprehensively evaluate the pathology of the lower extremity arteries across their entire length in subjects dying with abundant risk factors and to evaluate the clinical and imaging implications of the pathological characteristics. Lower extremity peripheral arterial disease is a major cause of cardiovascular morbidity, but a systematic characterization of the pathology has never been undertaken. Twelve legs were obtained from 8 cadavers with histories of coronary risk factors (median age 82 years, 6 men); 8 of 12 legs were evaluated using computed tomography before the major peripheral arteries were dissected along their entire length. Dissected arteries were cut serially at 3 to 4 mm, and a total of 2,987 sections were examined. Luminal irregularities and stenosis were more commonly seen in computed tomography images of above-the-knee (AK) arteries. Atherosclerotic lesions were histologically confirmed and were more common in AK (95.7%) than below-the-knee (BK) (56.8%) arteries. Occluded vessels were observed at 18 sites, including 8 AK and 10 BK arteries. Pathologically, acute thrombus was observed in all 8 AK sites, of which 3 were associated with plaque rupture and 5 were related to calcified nodules. The 10 occluded BK arteries revealed chronic total occlusions, of which one-half were embolic in origin and one-half were associated with atherosclerotic lesions. Intimal (75.3%) and medial (86.2%) calcifications were commonly encountered. Proportionate to the neointimal atherosclerosis, intimal calcification was more severe in AK arteries; the severity of medial calcification was no different between AK and BK arteries. Calcification was significantly greater in arteries excised from subjects with compared with those without diabetes. Atherosclerosis occurs more commonly in AK arteries and luminal occlusion from acute thrombosis secondary to rupture or calcified nodules. BK occlusion was chronic in nature, and at least one-half of lesions were embolic in origin. Medial calcification was similarly common in AK and BK arteries but more prevalent in subjects with diabetes. [Display omitted]